Key hepatic signatures of human and mouse nonalcoholic steatohepatitis: A transcriptome–proteome data meta-analysis - Pyo, Jeong Joo; Choi, Yongsoo (Frontiers in Endocrinology, 2022)
Background: Despite the global prevalence of nonalcoholic fatty liver disease (NAFLD), its pathophysiology remains unclear. In this study, we aimed to establish highly confident nonalcoholic steatohepatitis (NASH) gene signatures and elucidate the pathological mechanisms underlying NASH through a systematic meta-analysis of transcriptome and proteome datasets obtained from NASH patients and mouse models. Methods: We analyzed NASH transcriptome datasets from 539 patients and 99 mice. Whole-liver tissue proteome dataset was used to confirm the protein level dysregulation of NASH signatures significant in both humans and mice. Results: In total, 254 human and 1,917 mouse NASH gene signatures were established. Up-regulated genes of 254 human signatures were associated with inflammation, steatosis, apoptosis, and extracellular matrix organization, while down-regulated genes were associated with response to metal ions and lipid and amino acid metabolism. When different mouse models were compared against human, models with high fat and high fructose diet most well resembled the genetic features of human NAFLD. Cross-species analysis revealed 66 genes to be concordantly dysregulated between human and mouse NASH. Among these, 14 genes were further validated to be dysregulated at the protein level. The resulting 14 genes included some of the well-established NASH associated genes as well as a promising NASH drug target. Functional enrichment analysis demonstrated that dysregulation of amino acid metabolism was the most significant hepatic perturbation in both human and mouse NASH. Conclusions: We established the most comprehensive hepatic gene signatures for NASH in humans and mice to date. To the best of our knowledge, this study is the first to collectively analyze the common signatures between human and mouse NASH on a transcriptome–proteome scale.